2021
DOI: 10.1039/d1fo02172a
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila and its outer protein Amuc_1100 regulates tryptophan metabolism in colitis

Abstract: Dietary interventions, including dietary ingredients, nutrients and probiotics, exert anti-inflammation effects in ulcerative colitis (UC). Our previous study showed that Akkermansia muciniphila (Akk), a promising probiotics, could protect against colitis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…A. muciniphila has been shown to influence the immune cell composition in mesenteric lymph nodes, shown by an increase in total B cell population and a decrease in total T cell and neutrophil populations [ 54 ]. Studies have demonstrated that A. muciniphila highly correlated with IL-10 in vivo and in vitro; both live and pasteurized A. muciniphila could restore the downregulation of IL-10 in UC mice and in H7N9-infected mice [ 55 , 56 ]. In vitro, A. muciniphila could increase IL-10 release in whole blood ex vivo LPS-stimulated mice as well as Porphyromonas gingivalis -infected bone marrow macrophages (BMMϕ) [ 54 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. muciniphila has been shown to influence the immune cell composition in mesenteric lymph nodes, shown by an increase in total B cell population and a decrease in total T cell and neutrophil populations [ 54 ]. Studies have demonstrated that A. muciniphila highly correlated with IL-10 in vivo and in vitro; both live and pasteurized A. muciniphila could restore the downregulation of IL-10 in UC mice and in H7N9-infected mice [ 55 , 56 ]. In vitro, A. muciniphila could increase IL-10 release in whole blood ex vivo LPS-stimulated mice as well as Porphyromonas gingivalis -infected bone marrow macrophages (BMMϕ) [ 54 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, SCFA released by gut microbiota has become a hot spot in the research of OP because it plays an important role in regulation of osteoclast metabolism and bone homeostasis 44 . Therefore, besides untargeted metabolomics in serum, SCFAs metabolomics analysis in feces was also carried out in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 47 Since the discovery of Amuc 1100, many favorable effects of A. muciniphila on host health have been attributed to the protein. These include anti-inflammatory and anti-tumorigenesis activity in DSS/azoxymethane treated mice, 79 restoration of aberrant tryptophan levels in colitis mice, 80 up-regulation of serotonin (i.e., 5-HT) metabolism in RIN-14B and Caco-2 cells, 81 and improvement of depression-like behavior in chronic stress-induced mice. 82 The beneficial health effects observed with a single, purified, A. muciniphila protein have expanded prospects for the commercialization of A. muciniphila , particularly in light of the difficulty encountered in culturing live, whole bacteria in bulk.…”
Section: A Muciniphila As a Biotherapeutic Agent: The Missin...mentioning
confidence: 99%